2020
DOI: 10.1111/jdi.13247
|View full text |Cite
|
Sign up to set email alerts
|

Activation of overexpressed glucagon‐like peptide‐1 receptor attenuates prostate cancer growth by inhibiting cell cycle progression

Abstract: Aims/Introduction Incretin therapy is a common treatment for type 2 diabetes mellitus. We have previously reported an anti‐prostate cancer effect of glucagon‐like peptide‐1 receptor (GLP‐1R) agonist exendin‐4. The attenuation of cell proliferation in the prostate cancer cell line was dependent on GLP‐1R expression. Here, we examined the relationship between human prostate cancer severity and GLP‐1R expression, as well as the effect of forced expression of GLP‐1R using a lentiviral vector. Materials and Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 36 publications
(63 reference statements)
0
14
0
Order By: Relevance
“…Western blotting was performed as described previously [ 13 ]. The following primary antibodies were used: Cyclin D1 (#2978; Cell Signaling Technology, Danvers, MA, USA) and β-actin (sc-47778; Santa Cruz Biotechnology, Santa Cruz, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Western blotting was performed as described previously [ 13 ]. The following primary antibodies were used: Cyclin D1 (#2978; Cell Signaling Technology, Danvers, MA, USA) and β-actin (sc-47778; Santa Cruz Biotechnology, Santa Cruz, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…RT and quantitative real-time PCR were performed as described previously [ 13 ]. Each sample was analyzed in triplicate and normalized against hypoxanthine phosphoribosyltransferase ( HPRT ) mRNA expression.…”
Section: Methodsmentioning
confidence: 99%
“…50 Forced expression of GLP-1 receptor attenuates prostate cancer cell proliferation by inhibiting cell cycle progression in vitro and in vivo. 51 A recent study also showed that an anticancer drug and liraglutide decreased the viability of prostate cancer cells (LNCaP) synergistically. 52 To date, there are no reports relating liraglutide to an increased risk of prostate cancer.…”
Section: Prostate Cancermentioning
confidence: 99%
“…In the 30 human samples of PC GLP-1 receptor expression was inversely associated with cancer progression (Gleason score). Additionally in vitro and in vivo antiproliferative effects of GLP-1 receptors in ALVA-41 cells were evaluated and revealed that the presence of GLP-1 receptors inhibits PC cell proliferation by suppressing cell cycle progression [ 109 ]. Furthermore, the study of He and Li reveals that Exendin-4 sensitizes prostate cancer cells to radiation.…”
Section: Incretinsmentioning
confidence: 99%